LEARNING MOTIVATION AND SELF-REGULATED LEARNING IN HIGH SCHOOL STUDENT - Apridelia, Zana; Kardo, Rici; Dianto, Mori; Akintomide, Gabriel Akinjide (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
The formulation of problems in the study include: (1) Students who procrastinate in making assignments and there are students who do not complete assignments on time (2) Students who do not have motivation in themselves (3) Students who do not have life goals and there are students who cannot control themselves. The purpose of the study was to determine the level of learning motivation possessed by students in self-regulated learning and to determine the relationship between the two The type of research used is quantitative with a correlational approach. The research data population amounted to 55 high school students. The results of the study with 55 students were taken through questionnaire distribution techniques using a learning motivation scale and a self regulated learning scale. The results of the learning motivation questionnaire showed a high category (76.36%) with a frequency of 42 students, quite high (23.64%) with a frequency of 13 students. Then the level of self-regulated learning shows a high category (80.00%) with a frequency of 44 students, quite high (14.55%) with a frequency of 8 students, very high (3.63%) with a frequency of 2 students, and low (1.82%) with a frequency of 1 student. Based on the results of the study, it states that there is a significant relationship between learning motivation and self-regulated learning of high school students. This means that the higher the level of learning motivation of students, the higher the self-regulated learning.